DAYA SAING AGRIBISNIS UBI JALAR CILEMBU DI DESA CILEMBU, KECAMATAN PAMULIHAN, KABUPATEN SUMEDANG, JAWA BARAT - Welly Larasakti Handani; Lucyana Trimo (Universitas Galuh Ciamis, 2021)
Cilembu sweet potato is a superior commodity in Sumedang Regency which is financially profitable. Cilembu sweet potatoes have the best quality with superior sweetness so that demand for commodities continues to increase. Cilembu sweet potato faces obstacles related to fulfilling demand for commodities so that many sweet potatoes from other areas enter Cilembu Village. This study aims to determine the condition of the system and competitiveness of Cilembu sweet potato agribusiness in Cilembu Village, Pamulihan District, Sumedang Regency, West Java. The design of this research is qualitative with a case study research technique. Data collection methods used were observation, in-depth interviews, and literature. The analytical tool used is Porter's Diamond Theory, which has four main components and two supporting factors that interact with each other. From the results of the analysis, it can be seen that cilembu sweet potato agribusiness in Cilembu Village, Pamulihan District, Sumedang Regency, West Java has not had a competitive advantage because the linkages of competitiveness determinants that do not support each other are more dominant in this study. Only one of the six pairs of main components support each other, namely: the condition of the resource factor supports each other with the related Industry and the supporting industry, while the other main components do not support each other. The interaction of supporting components supports each other in several aspects, including the role of the government in mutually supporting the conditions of resource factors as well as related industries and supporting industries, while the opportunity component supports three main components, namely: related industries and supporting industries, demand conditions, and competition, structure. and strategy.